2008
DOI: 10.1177/0883073808314898
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Epilepsies and Epileptic Syndromes Among Children in Navarre, Spain: 2002 Through 2005

Abstract: All incident cases of children living in Navarre, Spain, younger than 15 years of age with newly diagnosed epilepsy (2002-2005) were registered in a prospective study, with epidemiologic and clinical data and complementary study results collected. Based on International League Against Epilepsy criteria, 191 patients were diagnosed as having epilepsy. The overall incidence rate is 62.6 cases per 100 000, with the highest incidence (95.3 cases per 100 000) during the first year of life. Fifty-five percent of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 24 publications
3
23
1
9
Order By: Relevance
“…• There is no high-level evidence to support any particular current agents for use in infants with seizures. Overall, infantile (epileptic) spasms constitute the largest single epilepsy subgroup, representing 13-45.5% of infantile population-based incidence studies 44,47,[52][53][54][55][56] For other seizure types there are limited data beyond case series (class 3 and 4 studies) The outcomes reported in typically class 4 studies suggest that seizures in infancy are predictive of comorbidities as well as complex and poor outcomes 52,53,55 Clinical semiology/ types of epileptic events…”
Section: Methodsmentioning
confidence: 99%
“…• There is no high-level evidence to support any particular current agents for use in infants with seizures. Overall, infantile (epileptic) spasms constitute the largest single epilepsy subgroup, representing 13-45.5% of infantile population-based incidence studies 44,47,[52][53][54][55][56] For other seizure types there are limited data beyond case series (class 3 and 4 studies) The outcomes reported in typically class 4 studies suggest that seizures in infancy are predictive of comorbidities as well as complex and poor outcomes 52,53,55 Clinical semiology/ types of epileptic events…”
Section: Methodsmentioning
confidence: 99%
“…Muitos estudos prévios sobre a prevalência e a incidência de epilepsia já foram publicados, com resultados variando de 0,9 a 57 casos por 1.000 habitantes para a prevalência, e 26 a 190 casos por 100.000 habitantes para a incidência [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . Muitas dessas variações ocorreram devido a diferenças metodológicas, como definição de epilepsia, critérios diagnósti-cos, ou avaliação prospectiva ou retrospectiva dos dados 27 .…”
Section: Discussionunclassified
“…Foi observada uma predominância de epilepsia idiopática, em relação à epilepsia sintomática (64%), resultados semelhantes a relatos pré-vios 8,12,13 . No entanto, outros autores observaram uma predominância de epilepsia criptogênica e/ou sintomática 2,3,6,7,14,15 . As diferenças entre os estudos podem ser decorrentes do fato de que alguns casos não puderam ser classificados pelas categorias detalhadas da classificação da ILAE 28 .…”
Section: Discussionunclassified
See 2 more Smart Citations